PENGEMBANGAN DESA WISATA BERBASIS PARTISIPASI MASYARAKAT LOKAL DI DESA WISATA JATILUWIH TABANAN, BALI - Made Heny Urmila Dewi (Universitas Gadjah Mada, 2013)
The development of rural tourism requires the participation of local communities in the entire developmentphases starting from the planning, implementation, and supervision. However, in reality, public participationis often completely overlooked. This study aims to examine the involvement of local communities in thedevelopment of rural tourism and formulate the model of tourism development which uphols the participationof local community. The study is conducted in rural tourism Jatiluwih, Tabanan Regency, Bali. The process ofcollecting data through the studi literature, in-depth interviews and non-participant observation. The analyticalmethod used is descriptive analysis. The result of the research indicates that the development of rural tourismin Jatiluwih still does not yet involve the local community. The role of government seems dominant, but whenreferring to the clean and sustainable governance approach, the role of the government is expected to becomea facilitator by providing bigger opportunity to take part as well as the bene????ts from the development to thelocal community. It is required the political will of the government to reduce the dominant role in developingrural tourism, through opening wider space for the community to participate.